The planning of the psychological preparation process in volleyball athletes. An imperative for the state of optimal disposition(Rewiev) (Revista científica Olimpia, 2020)
The purpose of this article is to make theoretical reflections on the importance of planning psychological preparation in volleyball athletes at school ages as a pedagogical and psychological process of developing the psychic qualities and properties of the athlete, necessary for the efficient realization of the sports activity in order to guarantee a state of psychological predisposition in the extreme conditions of training and competitions.
Keywords: psychological preparation; volleyball; state of psychic predisposition; psychological demands; planning